Use of Educational Game Media Calculations to Improve Summary Calculations in Students with Intellectual Disability - Paozan, Panji (JASSI ANAKKU, 2021)
This study aims to improve numeracy skills with intellectual disability students through numeracy educational games media. The research method used is Classroom Action Research using demonstration learning methods. The research subjects were 2 (two) people at the Border State Special School. The results of the study showed an increase in students' ability in addition to counting after using the media of numeracy educational games. Where the value of the results of the teaching and learning process shows an increase and is in accordance with the existing Minimum Completeness Criteria. The success of this numeracy educational game media is because it is interesting for students and easy to follow. This study demonstrates that the use of numeracy educational games is easy to understand and has an impact on increasing the numeracy ability with intellectual disability students.